The Effect of Problem Based Learning in Social Studies on Financial Literacy Material on the Knowledge Level of Ninth Grade Students at State Junior High School 13 in Semarang - Siska Anggraeni; Lukki Lukitawati (FKIP - Universitas Riau, 2026)
The low level of financial literacy in students' daily lives shows the need for learning innovations that can improve contextual understanding of concepts. This study aims to analyze the effect of applying the Problem Based Learning (PBL) model in Social Studies (IPS) learning on financial literacy material on the knowledge level of ninth-grade students at SMP Negeri 13 Semarang. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of two classes, namely the experimental class and the control class, with a total of 33 students. Data collection was conducted through pretest and posttest multiple-choice questions, then analyzed using normality tests, homogeneity tests, paired sample t-tests, and N-Gain. The results showed a significant increase in the experimental class with an average score increasing from 79.27 to 85.57 and a significance value of < 0.001. The N- Gain value of 0.3934 was in the moderate category. These findings indicate that the application of the PBL model had a positive and significant effect on increasing students' knowledge of financial literacy, although the effectiveness of the improvement was still moderate. The PBL model can be an alternative to contextual social studies learning to strengthen students' understanding of financial literacy.